2016
DOI: 10.1016/j.genrep.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corexit oil dispersants and the WAF of dispersed oil on DNA damage and repair in cultured human bronchial airway cells, BEAS-2B

Abstract: Large quantities of dispersants were used as a method to disperse the roughly 210 million gallons of spilled crude oil that consumed the Gulf of Mexico. Little is known if the oil-dispersant and oil-dispersant mixtures on human airway BEAS-2B epithelial cells. Here we present the cytotoxic and genotoxic in vitro effects on the human lung cells BEAS-2B following exposure to and oil-dispersant mixtures on human airway BEAS-2B epithelial cells. Here we present the cytotoxic and genotoxic in vitro effects on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our initial experiment with three female mice was designed to determine a dose of Corexit 9500+oil SAF that caused lung injury in mice. Previous experiments indicated that the Corexit 9500+oil and Corexit 9527+oil SAF displayed similar toxicity curves with BEAS-2B cells in culture and that at 1/100 dilution of both solutions was toxic [ 27 ]. Therefore, mice were treated by oropharyngeal aspiration with 50µL of the 1/100 dilution SAF and 10-fold higher (1/10) and lower dilutions (1/1,000) SAF to assess their tolerability.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial experiment with three female mice was designed to determine a dose of Corexit 9500+oil SAF that caused lung injury in mice. Previous experiments indicated that the Corexit 9500+oil and Corexit 9527+oil SAF displayed similar toxicity curves with BEAS-2B cells in culture and that at 1/100 dilution of both solutions was toxic [ 27 ]. Therefore, mice were treated by oropharyngeal aspiration with 50µL of the 1/100 dilution SAF and 10-fold higher (1/10) and lower dilutions (1/1,000) SAF to assess their tolerability.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown an association between exposure to crude oil and adverse effects among spill responders ( Aguilera et al 2010 ; Laffon et al 2016 ), but no previous spill involved this level of dispersant use or resulted in an investigation of potential associations between dispersant use and adverse health effects. In vitro results suggested that 9527A and 9500A may have adverse effects on human lung tissue ( Major et al 2016 ; Shi et al 2013 ). Our results provide epidemiological evidence to suggest that exposure to 9527A or 9500A may be associated with adverse health effects, even after taking into account exposure to the crude oil.…”
Section: Discussionmentioning
confidence: 99%
“…Using in vitro cultures of human bronchial cells, Shi et al ( 2013 ) showed that exposure to either 9500A or 9527A resulted in a significant loss of cell viability and that the loss of viability was dose-dependent. Similarly, Major et al ( 2016 ) found that exposing human bronchial cells to individual mixtures of 9500A and 9527A with crude oil induced both cytotoxic and genotoxic effects. Although data on toxicity of dispersants are limited, there is some evidence of effects caused by the component ingredients of each dispersant.…”
Section: Introductionmentioning
confidence: 90%
“…The neutral comet assay, a standard and sensitive technique to analyse DNA DSBs, was used in BEP2D cells. 36 BEP2D cells were treated with exosomes following 2 Gy irradiation and transfected with 50 and 100 nM miR-1246 mimic or mimic-NC for 24 h, respectively. Then, cells were trypsinised and resuspended in 1× PBS to a final concentration of 1×10 4 cells/mL.…”
Section: Methodsmentioning
confidence: 99%